2021
DOI: 10.1038/s41598-021-87007-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sr deficiency on structural and electrical properties of SrTiO3 thin films grown by metal–organic vapor phase epitaxy

Abstract: Homoepitaxial growth of SrTiO3 thin films on 0.5 wt% niobium doped SrTiO3 (100) substrates with high structural perfection was developed using liquid-delivery spin metal–organic vapor phase epitaxy (MOVPE). Exploiting the advantage of adjusting the partial pressures of the individual constituents independently, we tuned the Sr/Ti ratio of the gas phase for realizing, stoichiometric, as well as Sr deficient layers. Quantitative energy dispersive X-ray spectroscopy in a scanning transmission electron microscope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…No contrast fluctuations are observed within the film indicating homogeneous and coherent film growth. This is verified by high-resolution transmission electron microscopy (HRTEM) measurements, presented in Figure 2b, which also display an atomically sharp SrSnO 3 /NdScO 3 interface seen along [1][2][3][4][5][6][7][8][9][10] direction and no extended defects in the SrSnO 3 film. On the other side, a strong dark contrast occurs at the interface between the undoped BaSnO 3 and SrSnO 3 layers and a large amount of threading dislocations is visible in the BaSnO 3 film (Figure 2a), which lead to the formation of strong strain fields at the BaSnO 3 /SrSnO 3 interface.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…No contrast fluctuations are observed within the film indicating homogeneous and coherent film growth. This is verified by high-resolution transmission electron microscopy (HRTEM) measurements, presented in Figure 2b, which also display an atomically sharp SrSnO 3 /NdScO 3 interface seen along [1][2][3][4][5][6][7][8][9][10] direction and no extended defects in the SrSnO 3 film. On the other side, a strong dark contrast occurs at the interface between the undoped BaSnO 3 and SrSnO 3 layers and a large amount of threading dislocations is visible in the BaSnO 3 film (Figure 2a), which lead to the formation of strong strain fields at the BaSnO 3 /SrSnO 3 interface.…”
Section: Introductionsupporting
confidence: 62%
“…depending on their chemical composition and crystal structure. [1][2][3][4][5] In addition, electrical properties of perovskites can easily be manipulated by doping and/or incorporation of lattice strain, which enables their use in various applications. [6,7] However, the main challenge has been their high carrier density and low mobility.…”
Section: Introductionmentioning
confidence: 99%
“…Our work evidences the lack of semiconductor-like properties in the absence of such processing. Concurrently, in the last years, it has been found that structural or compositional defects, other than oxygen vacancies/substitutions, can drive the electronic properties of STO towards semiconductor state 49 54 . We believe that during high-temperature processes, such defects can unintentionally form and lead to the increased optical absorption and electrical conductivity.…”
Section: Resultsmentioning
confidence: 98%
“…As a rule, the novel functional materials are very often created on the platform of complex oxides 1 3 . The main advantage of oxides is their chemical stability during operation of the material in an air atmosphere 4 .…”
Section: Introductionmentioning
confidence: 99%